Distribuição da castanha-do-brasil (Bertholletia excelsa) através do tempo: desde a contração no refúgio glacial, sua expansão mediada pelos humanos, até a mudança climática antropogênica - Thomas, Evert; Caicedo, Carolina Alcázar; Loo, Judy; Kindt, Roeland (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Brazil nut (Bertholletia excelsa) is one of the most important non-timber forest producing tree species in the Amazon. One aspect related to the sustainability of Brazil nut that has so far received very limited attention in literature is how the species’ distribution has changed through time and will continue to do so in light of anthropogenic climate change. We modeled the potential distribution of Brazil nut during different past climates as well as during several future time periods. Of the past time periods, the Last Glacial Maximum ( 21,000 BP) had the biggest impact on the present distribution of Brazil nut. The distribution of suitable habitat may have been restricted primarily to several potential refugia across southern Amazonia. On the other hand, the oldest Brazil nut remains found at the Pedra Pintada cave ( 11,000 BP) were probably harvested by early humans from trees that reached the area after natural range expansion from one or more smaller refugia which may have been located close to the Amazon River delta. Future climate projections predict a positive future for Brazil nut. We conclude with a number of recommendations to improve the species’ conservation, use and management, both within and outside its current distribution area.